Discovery of VHE emission towards the Carina arm region with the H.E.S.S. telescope array: HESS J1018-589 - Abramowski, A. (2012)
The Carina arm region, containing the supernova remnant SNR G284.3-1.8, the high-energy (HE; E > 100 MeV) binary 1FGL J1018.6-5856 and the energetic pulsar PSR J1016-5857 and its nebula, has been observed with the H.E.S.S. telescope array. The observational coverage of the region in very-high-energy (VHE; E > 0.1 TeV) γ-rays benefits from deep exposure (40 h) of the neighboring open cluster Westerlund 2. The observations have revealed a new extended region of VHE γ-ray emission. The new VHE source HESS J1018-589 shows a bright, point-like emission region positionally coincident with SNR G284.3-1.8 and 1FGL J1018.6-5856 and a diffuse extension towards the direction of PSR J1016-5857. A soft (Γ = 2.7 ± 0.5stat)photon index, with a differential flux at 1 TeV of N0 = (4.2 ± 1.1) × 10-13 TeV^{-1} cm^{-2} s^{-1} is found for the point-like source, whereas the total emission region including the diffuse emission region is well fit by a power-law function with spectral index Γ = 2.9 ± 0.4stat and differential flux at 1 TeV of N_0 = (6.8 ± 1.6) × 10^{-13} TeV^{-1} cm^{-2} s^{-1}. This H.E.S.S. detection motivated follow-up X-ray observations with the XMM-Newton satellite to investigate the origin of the VHE emission. The analysis of the XMM-Newton data resulted in the discovery of a bright, non-thermal point-like source (XMMU J101855.4-58564) with a photon index of Γ = 1.65 ± 0.08 in the center of SNR G284.3-1.8, and a thermal, extended emission region coincident with its bright northern filament. The characteristics of this thermal emission are used to estimate the plasma density in the region as n ≈ 0.5 cm-3 (2.9 kpc/d)2. The position of XMMU J101855.4-58564 is compatible with the position reported by the Fermi-LAT collaboration for the binary system 1FGL J1018.6-5856 and the variable Swift XRT source identified with it. The new X-ray data are used alongside archival multi-wavelength data to investigate the relationship between the VHE γ-ray emission from HESS J1018-589 and the various potential counterparts in the Carina arm region.